SWITCHING DEFENSE - Scariolo, Sergio (Sport- és Egészségtudományi füzetek, 2025)
We are using switching defense in different moments of the game. We can have a team which is suited to run this de-fense or we can use it for a few possessions to receive some advantage. If we don’t have a player in position five who can contain the ball well, the coach has to reduce the goals the player has to focus on. That focus has to be on the ball and to slow it down. There is a difference between using the switching and abus-ing. It is not for saving energy, it is for attacking and making trouble for the offense. To achieve that, there has to be a rule. For example, four switches when 10 seconds left from the shot clock or five switches when 5 seconds left from the shot clock. It puts responsibility on all the players and they can not blame poor communication.